Stimulasi Membaca Permulaan pada Anak Usia Dini dengan Menggunakan Flash Card Digital - Rahmah Novianti; Niken Pratiwi (Jurnal Ilmiah POTENSIA, 2024)
Language development is very important for early childhood because through language children can communicate and interact with others. One of the abilities of language development is early reading skills. This research aims to develop media for beginning reading activities using digital media in the form of flash cards as a media of stimulation for early childhood in early reading skills. This type of research is development research using ADDIE model. The method used for data collection are observation and instruments. This research data was analyzed descriptively quantitatively. The research results showed that the value obtained from material experts was 84% and 86% from media experts. Based on this, digital media in the form of word cards is suitable for testing in early childhood learning activities. The implications of this research are that digital flash cards can be used by teachers in the learning process.